Acomodative Infiltrative Educational Culture of Transnational Salafi on Zād Al-Ma'ād Pesantren in Palembang Indonesia - Munir, Munir; Siraj, Fuad Mahbub; Arif, Ridwan; Jamil, Syahril; Qaaf, Muhammad Alfath (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research aimed to understand the characteristics of the pesantren’s culture, which is based on transnational culture. This study utilized a mixed-methods approach, including interviews with pesantren leaders and students and participant observations within the pesantren community. The findings revealed that transnational culture within pesantren is influenced by global Islamic discourses and practices while maintaining traditional Indonesian cultural elements. Understanding these characteristics is crucial for policymakers and educators to address the evolving landscape of Islamic education in Indonesia. Further research is needed to explore the impact of transnational culture on the development of pesantren in the future. The Salafi’s Islamic Boarding School, Zād al-Maʿād, was chosen as the research site for that purpose. The approach employed in this research is cultural anthropology with data collection tools in documentation studies, observations, and interviews. The findings emphasize the adaptability of Salafi pesantren to local customs and traditions, showcasing a unique blend of global ideology and local practices that contribute to the movement's continued success in Indonesia. Based on qualitative analysis, the boarding school is also an agent of Islamic preaching in spreading Salafi’s understanding and a center for the cadre of Salafi’s preachers from a young age. The Salafi’s network can use its program to organize various international programs.